(untitled) (Transport systems and technologies, 2018)
Based on the analysis of the needs and the state of development of devices that provide intellectualization of energy, the model of intelligent information system of the railway power supply network management system is proposed. The model corresponds to the latest trends in the intellectualization of control systems in the electric power industry. The development of the model was carried out with the purpose of rational use of the technical equipment of the computer network of the system of electricity supply of rail transport and the introduction of additional functional. The model focuses on the development of an existing information system based on the concept of Smart Grid and a single information space. The feature of the proposed model is a subsystem of automated control of power consumption, which is based on the implemented information gathering devices and the automated system of commercial electricity accounting. The subsystem is intended to save money by using a differentiated tariff for the zones of the day.